PCR based mutation screening of the laminin alpha2 chain gene (LAMA2): application to prenatal diagnosis and search for founder effects in congenital muscular dystrophy. Issue 3 (March 1998) - Guicheney, P; Vignier, N; Zhang, X; He, Y; Cruaud, C; Frey, V; Helbling-Leclerc, A; Richard, P; Estournet, B; Merlini, L; Topaloglu, H; Mora, M; et al.
Abstract : Classical congenital muscular dystrophy with merosin deficiency is caused by mutations in the laminin alpha2 chain gene (LAMA2). Extended sequencing of the introns flanking the 64 LAMA2 exons was carried out and, based on these sequences, oligonucleotide primers were designed to amplify the coding region of each exon separately. By PCR-SSCP analysis, we identified eight new mutations in nine families originating from various countries. All induced a premature truncation of the protein, either in the short arm or in the globular C-terminal domain. A 2 bp deletion in exon 13, 2098delAG, was found in three French non-consanguineous families and a nonsense mutation of exon 20, Cys967stop, in two other non-consanguineous families originating from Italy. Determination of rare intragenic polymorphisms permitted us to show evidence of founder effects for these two mutations suggesting a remote degree of consanguinity between the families. Other, more frequent polymorphisms, G to A 1905 (exon 12), A to G 2848 (exon 19), A to G 5551 (exon 37), and G to A 6286 (exon 42), were used as intragenic markers for prenatal diagnosis. This study provides valuable methods for determining the molecular defects in LAMA2 causing merosin deficient congenital muscular dystrophy.